2004
DOI: 10.1126/science.1099472
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Link with Asthma in Mice Congenitally Deficient in Eosinophils

Abstract: Eosinophils are often dominant inflammatory cells present in the lungs of asthma patients. Nonetheless, the role of these leukocytes remains poorly understood. We have created a transgenic line of mice (PHIL) that are specifically devoid of eosinophils, but otherwise have a full complement of hematopoietically derived cells. Allergen challenge of PHIL mice demonstrated that eosinophils were required for pulmonary mucus accumulation and the airway hyperresponsiveness associated with asthma. The development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
590
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 646 publications
(619 citation statements)
references
References 26 publications
26
590
0
3
Order By: Relevance
“…Samples of whole blood and leukocytes isolated by dextran sedimentation and washed free from plasma (isolated) were stimulated with agonists. Red blood cells were lysed by NH 4 Cl, and shape change responses were analyzed by flow cytometry as increases in forward scatter of eosinophils and neutrophils. As compared with isolated cells, the potency of 5-oxo-ETE and eotaxin was reduced in whole blood, while the potency of PGD 2 and IL-8 was unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples of whole blood and leukocytes isolated by dextran sedimentation and washed free from plasma (isolated) were stimulated with agonists. Red blood cells were lysed by NH 4 Cl, and shape change responses were analyzed by flow cytometry as increases in forward scatter of eosinophils and neutrophils. As compared with isolated cells, the potency of 5-oxo-ETE and eotaxin was reduced in whole blood, while the potency of PGD 2 and IL-8 was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of whole blood, and buffy coats suspended in platelet-rich plasma (PRP), platelet-poor plasma (PPP) or phosphate-buffered salt solution (PBS) were stimulated with agonists. Red blood cells were lysed by means of NH 4 Cl and shape change responses were analyzed by flow cytometry as increases in forward scatter of eosinophils and neutrophils. The loss of 5-oxo-ETE bio-activity in whole blood was not reversed by depleting the red blood cells prior to stimulation (buffy coat in PRP) or additional depletion of platelets (buffy coat in PPP), but was prevented in the absence of plasma (buffy coat in PBS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The airway inflammation of asthma has a predominance of Th2 CD4 + lymphocytes, eosinophils and mast cells infiltrating the lung interstitium. Several studies indicate the existence of a mechanism dependent on IL-5 and eosinophils that induce pulmonary damage and intensify AHR [3][4][5]. In other studies, however, the induction of AHR was observed despite the absence of infiltrating eosinophils, suggesting dissociation between these phenomena [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%